2009
DOI: 10.1073/pnas.0900544106
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional neoteny in the human brain

Abstract: In development, timing is of the utmost importance, and the timing of developmental processes often changes as organisms evolve. In human evolution, developmental retardation, or neoteny, has been proposed as a possible mechanism that contributed to the rise of many human-specific features, including an increase in brain size and the emergence of human-specific cognitive traits. We analyzed mRNA expression in the prefrontal cortex of humans, chimpanzees, and rhesus macaques to determine whether human-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
321
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 352 publications
(349 citation statements)
references
References 34 publications
23
321
2
3
Order By: Relevance
“…Interestingly, the GO categories that exhibit the highest rates of evolution include "regulation of transcription, DNA-dependent," "negative regulation of transcription from RNA polymerase II promoter," and "multicellular organismal development." This squares nicely with previous reports arguing that many of the extant differences between modern humans and chimpanzees involve changes in gene regulations and neoteny (36).…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, the GO categories that exhibit the highest rates of evolution include "regulation of transcription, DNA-dependent," "negative regulation of transcription from RNA polymerase II promoter," and "multicellular organismal development." This squares nicely with previous reports arguing that many of the extant differences between modern humans and chimpanzees involve changes in gene regulations and neoteny (36).…”
Section: Discussionsupporting
confidence: 51%
“…cortices show a protracted postnatal developmental course relative to other regions (26)(27)(28). Because many of the frontotemporal regions where SA appears to be most sensitive to BW variation within MZ twins have been separately implicated in multiple common psychiatric disorders (42,43), our data also propose a potential neurodevelopmental mechanism for the observed association between normative BW variation in fullterm pregnancies and later risk for psychopathology (7).…”
Section: Modeling Prenatal Environmental Influences On Brain Developmentmentioning
confidence: 55%
“…Environmentally determined disturbances of such early processes could well have behaviorally relevant consequences for cortical development throughout the lifespan (25), which may be accompanied by neuroanatomical alterations detectable by in vivo neuroimaging. Prefrontal cortices are particularly salient in this regard given their protracted maturational course (26)(27)(28) and involvement in multiple domains of higher cognition. To provide a detailed picture of the relationship between BW variation and postnatal cortical development, we used "surface-based morphometry," to measure three distinct morphometric properties of the cortical sheet from sMRI: cortical volume (CV) and its two sole determinants [mean cortical thickness (CT) and total cortical surface area (SA)].…”
mentioning
confidence: 99%
“…In support of this hypothesis, it was recently shown that some, but not all, gene expression changes taking place during human postnatal prefrontal cortex (PFC) development showed timing differences relative to chimpanzees and macaques (Somel et al 2009). Although no specific mechanism associated with cognitive development was identified in that study, it reported that genes showing human-specific delays tended to be neuron-associated.…”
mentioning
confidence: 92%